Physicochemical properties of superfine grinding-microwave modified artichoke soluble dietary fiber and their alleviation of alcoholic fatty liver in mice - Wang, Yayi; He, Bian; Zhang, Linwei; Zhu, Renwei; Huang, Liang (Frontiers in Nutrition, 2023)
The effects of superfine grinding (SG) and microwave treatment (MT) on the structure and physicochemical properties of artichoke soluble dietary fiber (ASDF) and its protective effects on mice with alcoholic fatty liver (AFL) were studied. We compared the changes in structural characteristics and physicochemical properties of ASDF, SG-ASDF (ASDF treated by SG), MT-ASDF (ASDF treated by MT), and CM-ASDF (ASDF treated by SG and MT). Moreover, we evaluated the effects of the obtained ASDF on the growth characteristics, blood lipid levels, and liver of mice with AFL. Our results of the study showed that CM-ASDF had a more concentrated and uniform particle size, a higher extraction rate of ASDF and significantly improved water-holding capacity (WHC), oil-holding capacity (OHC) and water swelling capacity (WSC) of ASDF (p < 0.05). After the ASDF intervention, mice with AFL exhibited a significant improvement in body lipid levels and reduce liver inflammation.Specifically, aspartate aminotransferase (AST), alanine aminotransferase (ALT), malonaldehyde (MDA), Tumor necrosis factor-α (TNF-α)and Interleukin-6 (IL-6) were significantly decreased, while superoxide dismutase (SOD) and glutathione peroxidase (GSH-PX) were significantly increased (p < 0.05).And the hematoxylin-eosin (HE) staining results showed significant improvement of hepatic steatosis in mice with AFL. In summary, our study found that both SG and MT could improve the structure and physicochemical properties of ASDF, with CM-ASDF being the most effective. Additionally, CM-ASDF was selected to continue the investigation and demonstrated an excellent protective effect on mice with AFL, with the high dose group (H-ASDF) showing the greatest benefit. These findings provided some new insights for future comprehensive utilization of ASDF and drug development for the treatment of AFL.